Recombinant production of interleukin-1 receptor antagonist in fusion to albumin binding domain with potential affinity to human serum albumin - Fatemeh Shafiee; Ali Yazdani (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Anakinra must be injected daily due to its short half-life and this leads to lower patient compliance. Therefore, the aim of this study was to produce an interleukin-1 receptor antagonist (IL-1Ra) with albumin binding domain (ABD) as a novel fusion protein and evaluate its binding ability to albumin and its biological effects. Experimental approach: The three-dimensional structure of IL-1Ra-ABD was predicted by MODELLER software and its interaction with IL-1R was evaluated by the HADDOCK server. The expression of IL-1Ra-ABD was performed in E. coli in fusion with intein 1 of pTWIN1 in soluble form and then purified. The affinity of IL-1Ra-ABD to human serum albumin (HSA) was determined on native-PAGE, and its release percent toward time was evaluated. Moreover, an MTT assay was used to determine the antagonizing properties of recombinant IL-1Ra-ABD against IL-1β in A375 and HEK293 cell lines. Findings/Results: The stable complex of IL-1Ra-ABD with IL-1R established the absence of steric hindrance due to the addition of ABD to IL-1Ra. The expression induction of intein 1-IL-1Ra-ABD using 0.1 mM IPTG at 15 °C, and its cleavage represented bands approximately in 50 and 23 kDa. Furthermore, about 78% of IL-1Ra-ABD was attached to the HSA after 2 h of incubation, and the MTT assay showed no significant differences between the effects of IL-1Ra-ABD and native IL-1Ra in cell survival. Conclusions and implications: The production of soluble IL-1Ra-ABD with no significant differences in IL-1Ra antagonizing effects was successfully performed. IL-1Ra-ABD showed suitable interaction with HSA and was released over time. However, the half-life of IL-1Ra-ABD in vivo must be determined in the subsequent investigations.